Embodying the sacred: women mystics in seventeenth-century Lima - Van Deusen, Nancy E. (Duke University Press, 2018)
Material and immaterial embodiment -- Rosa de Lima and the imitatio morum -- Reading the body: mystical theology and spiritual actualization in early seventeenth-century Lima -- Living in an (im)material world: Angela de Carranza as a reliquary -- The relational self -- Carrying the cross of Christ: donadas in seventeenth-century Lima -- María Jacinta Montoya, Nicolás de Ayllón, and the unmaking of an Indian Saint in late seventeenth-century Peru -- Amparada de mi libertad: Josefa Portocarrero Laso de la Vega and the meaning of free will